Examining the role of intelligence quotient in predicting senior secondary school students’ achievement in chemistry - Ejovwokoghene Avwiri, Hannah; Enwefa, Chiekem; Ejakpomeghwe Odiri, Onoshakpokaiye (International Journal of Evaluation and Research in Education (IJERE), 2025)
The study examines the role of intelligence quotient (IQ) in predicting academic achievement in chemistry among senior secondary school students. The purpose of the study is to determine i) whether IQ predict chemistry achievement scores of senior secondary school students in chemistry and ii) the proportion of senior secondary school students’ chemistry achievement is attributable to the IQ areas of logical thinking, spatial intelligence, numerical, and verbal aptitude. The study’s research design was a correlation. The study was guided by two research questions and two null hypotheses. The study included 1,022 senior secondary school chemistry students as its population. A sample of 320 senior secondary school chemistry students was chosen using random sampling methods from 10 public schools. Three experts validated the intelligence quotient test (IQT), which was used as the data gathering tool. IQT’s dependability was determined to be 0.68 utilizing Kuder-Richardson formula 20 (KR-20). Both simple and multiple linear regressions were used to examine the collected data. Among other things, the study’s results showed that students’ IQ predicted 1.3% of the variation in their chemistry achievement. The results showed that the four components of IQ—numerical, aptitude, spatial, and logical—all significantly influence students’ achievement in chemistry. Additionally, students’ IQ substantially influenced their chemistry achievement ratings. Since chemistry achievement is heavily influenced by numerical, aptitude, spatial, and logical intelligence, students might benefit from specialized teaching strategies that support these domains. The addition of IQ test results as a requirement for enrollment in chemistry courses was suggested.